PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN FROZEN FOOD DI KOTA BATAM - Juniyanti; Asron Saputra (LPPM Universitas Putera Batam, 2022)
The aim of this research was to determine the effect of brand image and product quality onfrozen food purchasing decisions in Batam City. Data were obtained through questionnairesdistributed to people who shopped at Pasar Mitra Raya Batam City. The method used isdescriptive statistical analysis using SPSS version 26 software program. The yield of the ttest (partial) that brand image has a positive and significant effect on purchasing decisionswith t count > t table with a significance < 0.05, namely 11, 038 > 1,976 and a significant of0.000 <0.05, product quality has a positive and significant effect on purchasing decisionswith t count 5.038 > t table 1.976 where sig. 0.000 < 0.05. This is evidenced from the yieldof the F test where F count > F table with a significance of < 0.05, namely 255,073 > F table2.665 and sig 0.000 < 0.05 which states that brand image and product quality have a positiveand significant impact simultaneously on purchasing decisions. frozen food in Batam city.